2011
DOI: 10.1002/polb.23028
|View full text |Cite
|
Sign up to set email alerts
|

Development of new high transparent hybrid organic–inorganic monoliths with surface engraved diffraction pattern

Abstract: Flexible hybrid xerogels bringing together high optical transparency up to 96%, low shrinkage down to 5.5%, very smooth surface (average roughness of about 0.3 nm) and thermal stability up to 200 °C were achieved as a result of the optimization of sol‐gel preparative method and a new combination of sol‐gel precursors. Two types of hybrid materials (hereafter referred, respectively, as urea‐silicate and amino‐alcohol‐silicate gels) were synthesized in this work. The shrinkage and the transparency of these mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 25 publications
6
23
0
Order By: Relevance
“…36 Table III shows the average values of the logarithm of resistivity (log ρ) and normalized capacitance from five samples of each OIH film (uncertainty is expressed for 95% confidence). Table III demonstrates that for all analyzed OIH film samples, ρ is between 10 6 and 10 8 cm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Table III shows the average values of the logarithm of resistivity (log ρ) and normalized capacitance from five samples of each OIH film (uncertainty is expressed for 95% confidence). Table III demonstrates that for all analyzed OIH film samples, ρ is between 10 6 and 10 8 cm.…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36][37][38][39][40] Several studies have demonstrated 41-44 that the mechanical and electrical properties of these materials make them suitable pre-treatments to improve the corrosion resistance of several metals and alloys.…”
mentioning
confidence: 99%
“…If the drying of the gel occurs in wet supercritical conditions, the shrinkage will be minimal, and the resulting product is porous and is known as an aerogel [1,111,161]. The material is known as a monolith if the dimensions of the gel are greater than scarcely millimeters [1,[162][163][164]. In case of the gelation, it takes place by quick evaporation of the solvents; the materials obtained are coatings (Figure 3), films and fibers [14,154,165].…”
Section: -Methacryloxypropyltrimethoxysilane Maptsmentioning
confidence: 99%
“…The organic groups, through the combination of suitable monomers, may allow the formation of bridges between the silicate groups [175]. Examples of these types of products were reported by different authors [16,17,162,164]. In the last fifteen years, several review articles have been published in the design and application of OIH materials, and mostly were approached from the point of view of materials [2,3,12,27,36,112,148,[178][179][180][181][182].…”
Section: Hybrid Sol-gel Coatings For Corrosion Mitigationmentioning
confidence: 99%
“…The OIH gel matrices were prepared following a well-established methodology described elsewhere [28][29][30]. Two sets of four different structural types of ureasilicate OIH gel matrices were prepared by a reaction between the isocyanate group of the derived siloxane (ICPTES) with four different di-amino functionalized polyether (Jeffamine® D-400, Jeffamine® ED-600, ED-900 and ED-2000, hereafter generically referred as Jeffamines) with different molecular weights, with and without incorporated Cr(III) ions, obtained by adding the correspondent salt aqueous solutions with a concentration of 0.01M.…”
Section: Reagentsmentioning
confidence: 99%